From demo to delivery the process of production - Katz, Robert A.; Hepworth-Sawyer, Russ (Elsevier/Focal Press, 2009)
From Demo to Delivery: The Process of Production discusses each stage of the typical music production process from start to finish. Beginning with the creation and development of the composition and song production, the book then traces the process from the recording, mixing and mastering stages through to marketing and distribution. This book is a must read for anyone who wants to learn the pro techniques involved in creating music from start to finish. Packed with essential information, including signposts to other sources of information at the end of each chapter, From Demo to Delivery provides a map for musicians, semi-pro and aspiring producers, engineers and music professionals interested in learning how music makes it from the an idea to the page to the studio to a demo and into the hands of the market and beyond. Check out the book's website - http://demo2delivery.com/ *A start to finish guide of the production process, to understand and be in control of recordings *Contributing authors are experts in their field, readers can learn and get insight from the best *Accompanying website with audio examples, aid understanding being able to hear what is being discussed.
Includes bibliographical references (page 306) and index. - Print version record
Keywords: Sound recordings -- Production and direction; Sound -- Recording and reproducing; Sound recordings -- Marketing; Music trade -- Vocational guidance; Son; Enregistrement et reproduction; Musique; Industrie; Orientation professionnelle; MUSIC; Recording & Reproduction; Music trade; Vocational guidance; Sound; Recording and reproducing; Sound recordings; Marketing; Sound recordings; Production and direction; Tonträgerproduktion; Tonträgerhandel; Musikinspelning; Ljudupptagningar; marknadsföring; Musikbranschen